The Role of Hospital Management Information Systems (SIMRS), Work Discipline, and Organizational Culture in Enhancing Nurses’ Performance - Herkulanus Robi; Haddan Dongoran; Ayu Laili Rahmiyati (SAFE-Network, 2026)
This study aims to analyze the effect of the implementation of Hospital Management Information Systems (HMIS), work discipline, and organizational culture on nurses' performance at the Regional Public Hospital of Landak, West Kalimantan. The study is motivated by the increasing demand for high-quality health services, requiring hospitals to be supported by effective information systems, disciplined human resources, and a strong organizational culture. This research employed a quantitative approach with a sample of 125 nurses selected using a specific sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the help of SPSS after passing validity and reliability tests. The results show that the implementation of HMIS, work discipline, and organizational culture partially have a positive and significant effect on nurses' performance. Simultaneously, the three variables also have a significant effect on nurses' performance. These findings indicate that improving nurses' performance is not only influenced by technological aspects through the implementation of HMIS, but also by disciplined work behavior and an organizational culture that supports a professional and collaborative work environment. Therefore, hospitals need to continuously strengthen the implementation of HMIS, improve work discipline, and build a conducive organizational culture to support the improvement of healthcare service quality.